Percepción y actitud de los estudiantes universitarios respecto al cambio climático - Miranda Velázquez, Elizabeth; Betancourt Quintero, Bárbara; Reyes Romero, José; Gallegos Gallegos, Edith; Velásquez Morocho, Brenda; Santos Luna, Jovanny Angelina (My University, 2021)
Climate change constitutes a danger to global human and environmental health. Health personnel must exercise protection, promotion, surveillance and prevention functions, taking into account the competencies, skills and attitudes they acquired to join as professionals in the field of health, therefo-re, they must promote community eco-strategies in environmental education to its preservation. The present study identified the perception and attitu-de towards climate change of university nursing students of the Technical University of Machala. Scientific, cross-sectional, descriptive and analytical research carried out in the university population of the nursing career du-ring the months of May - September 2019. The sample size was 287 subjects. Simple random sampling was applied, with a guaranteed questionnaire of fifteen closed questions on a Likert scale. The percentage of information was evidenced as follows: 32 students stated that climate change arises from na-tural and human causes, which corresponds to 11.15% of the total population studied. Furthermore, we found that not all students adopted individual me-asures to mitigate environmental risks, but they do know about their causes and effects. Health personnel must disseminate to the community the crea-tion of healthy environments to prevent diseases and save the planet from environmental degradation, in addition, design an environmental education program, whose actions are aimed at making the individual aware of the importance of modifying their attitudes towards environmental problems raised today.
El cambio climático constituye un peligro para la salud humana y ambiental global. El personal de salud debe ejercer funciones de protección, promoción, vigilancia y prevención, teniendo en cuenta las competencias, habilidades y actitudes que adquirieron para incorporarse como profesionales en el cam-po de la salud, por lo tanto, debe fomentar ecoestrategias comunitarias en educación ambiental para su preservación. El presente estudio identificó la percepción y actitud frente al cambio climático de los estudiantes universita-rios de Enfermería de la Universidad Técnica de Machala. Investigación cien-tífica, transversal, descriptiva y analítica efectuada en la población univer-sitaria de la carrera de Enfermería durante los meses de mayo - septiembre del 2019. El tamaño de la muestra fue de 287 sujetos. Se aplicó un muestreo aleatorio simple, con cuestionario avalado de quince preguntas cerradas en escala Likert. El porcentaje de información, se evidenció así: 32 alumnos plasmaron que el cambio climático surge por causas naturales y humanas lo que corresponde al 11,15% de la población total estudiada. Además, encon-tramos que no todos los estudiantes adoptaron medidas individuales para mitigar los riesgos ambientales, pero sí conocen de sus causas y efectos. El personal de salud debe difundir a la comunidad la creación de entornos sa-ludables para prevenir enfermedades y salvar al planeta de la degradación ambiental, además, diseñar un programa en educación ambiental, cuyas ac-ciones estén orientadas a que el individuo tome conciencia de la importancia de modificar sus actitudes frente a las problemáticas ambientales suscitadas en la actualidad
Keywords: CAMBIO CLIMATICO; SALUD AMBIENTAL; EDUCACIÓN PARA LA SALUD